Recettes Alimentaires A Base Des Graines De Boscia Senegalensis Au Niger : Cas Des Communes De Bambeye Et Banibangou - Haoua Sabo; Maman Nafiou Aminou Illia; Maman Moustapha Rabiou; Aminatou Bako Maazou; Soumana Douma; Issa Chaibou; Ibrahim Amoukou; Hamidou Idrissa (European Scientific Journal, ESJ, 2018)
Food insecurity is an almost permanent reality in Niger due to climatic hazards. This study is a contribution to the capitalization and enhancement of Community know-how in the exploitation of natural resources and addresses the role of spontaneous foods of plant origin in the search for diversity and dietary balance, specifically the potentialities of Boscia senegalensis. It is a species whose different parts are used for many purposes in Niger. The different recipes based on immature seeds processed in two departments of Niger, Banibangou and Bambèye are listed. To this end, a questionnaire was sent to 128 women in Bambèye and 114 in Banibangou. The recipes identified are those implemented by women from these different communities. A total of 7 recipes as well as their ingredients and methods of preparation have been identified. One is made from seeds only. Three (3) recipes are prepared in association with millet, cowpea, Gynandropsis gynandra leaves and Maerua crassifola. For two (2) recipes, the seeds are taken back with milk. Finally, one (1) recipe using Boscia senegalensis bark and Guéra senegalensis leaves is used in postpartum women. In view of these results, it would be important to create the conditions for maintaining them, for their sustainable use, for their inclusion in agricultural and food statistics and for the dissemination of these revenues in other regions.